Investigating veterinary antiparasitic drugs as emerging contaminants in Irish groundwater - Mooney, Damien Thomas (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2021)
Due to increased intensification of the food production system, veterinary drugs have become a critical component in animal husbandry in Ireland and more broadly within the European Union. The administration of such substances can potentially lead to their occurrence in the environment, primarily as a result of the direct excretion on land, or excretion in faeces and urine which is subsequently land spread in manure or slurry. This work specifically focuses on two groups of antiparasitic agents commonly used in Irish agriculture, the anthelmintics and the anticoccidials, covering a total of 66 antiparasitic drugs. Anthelmintic drugs are used to control helminthic parasites (nematodes, cestodes and trematodes) that infect animals, particularly those exposed through pasture-based production systems, such as cattle and sheep. Anticoccidials are used to control coccidiosis and other protozoan infections in food producing animals, with primary prophylactic use in poultry production. Very limited information is available on the occurrence of anthelmintics and anticoccidials in the environment, particularly in groundwater, which has resulted in them being considered potential emerging organic contaminants of concern. Information on their environmental transformation products is even more scant. This dearth of information has been attributed (in part) to a lack of suitable analytical methodologies. The overall aim of this research was to investigate the occurrence of these antiparasitic agents in Irish groundwaters, to help broaden the overall knowledge and understanding of the fate of these contaminants in the environment. This was achieved through the development and application of more sensitive and comprehensive analytical methods, as presented in this thesis. A multi-residue solid phase extraction (SPE) method was developed for the extraction of 40 anthelmintic compounds in surface water and groundwater, with determination using ultra-high-performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS). This method, which includes 27 parent drugs and 13 transformation products, was validated and applied in a spatial occurrence study comprising a total of 106 sites, including 88 groundwater and 18 surface waters. The groundwater sites were selected to be representative of different karstic and fractured bedrock aquifers. During spring of 2017, 17 out of 40 anthelmintics were detected, with one or more anthelmintic residues found at 22% of sites. Detected anthelmintic concentrations were of the order of 1- 41 ng/L. A temporal study carried out over 13 months highlighted the importance of anthelmintic usage patterns and meteorological events in controlling the occurrence of anthelmintics in groundwaters that are most sensitive to contamination. This work not only presents the most comprehensive method currently available (to the best of the author?s knowledge) for detecting anthelmintics in surface and groundwaters, it also reports on some of the first occurrences of these contaminants in Irish groundwater. A second SPE method was also developed for the determination of 26 anticoccidial compounds by UHPLC-MS/MS and allows for the simultaneous analysis of both the ionophore and synthetic anticoccidials, including several analytically problematic polar compounds which previously required separate analysis. This method was applied as part of a comprehensive spatial occurrence study during autumn 2018, in which water samples from sites representative of different source and pathway factors were analysed for anticoccidial drugs. Up to seven different compounds were detected at 24% of sites, at concentrations ranging from 1 to 386 ng/L. The anticoccidials detected were in line with expected usage, with statistical analysis indicating that poultry activity was a significant driver of anticoccidial occurrences. This work presents the most comprehensive and sensitive method for the determination of anticoccidial drugs in groundwater amongst current literature, and reports the first groundwater detections of several anticoccidials, not only in Ireland, but also in Europe and perhaps globally.
APPROVED
Keywords: Emerging organic contaminants; Veterinary antiparasitic agents; Anthelmintics; Anticoccidials; Food producing animals; Water trace chemical analysis; Solid Phase Extraction; Ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS); Environmental fate; Karst and fractured bedrock aquifers; Groundwater occurrence; Republic of Ireland